Culture in higher education: An empirical analysis of employee perceptions and behavioural outcomes in the UAE - Badreddine, Said; Alwada'n, Tariq; Razzaque, Mohammad Abdur; Kafri, Ala Al; Ammari, Hamsa Al; Hamdan, Adel (Edelweiss Applied Science and Technology, 2025)
This study explores the relationship between cybersecurity culture and employee behaviour in higher education institutions (HEIs) in the United Arab Emirates (UAE), using a cross-sectional, mixed-methods approach. The sample comprised 246 employees across faculty (43.5%), administrative staff (48%), and management (8.5%) roles, with varying levels of experience and technical readiness. Quantitative analyses revealed that perceived cybersecurity culture was the most significant predictor of behaviour (Spearman’s ρ = 0.62, p = 0.003), with behaviour scores ranging from 37.91 in “Developing Culture” contexts to 75.98 in “Exemplary Culture” settings. ANOVA results indicated significant differences in behaviour across role (F(2,83) = 5.72, p = 0.009) and experience levels (F(5,79) = 3.94, p = 0.021), with early-career staff scoring the lowest. Best practice adherence further explained behavioural variance (F(5,79) = 9.84, p < 0.001). Qualitative analysis identified three core challenges: restrictive system controls, outdated training, and leadership disengagement. These findings highlight the behavioural and contextual drivers of cybersecurity and emphasize the need for culture-first strategies that align institutional norms, communication, and leadership modelling with digital security objectives.